Controllability design of a memristive hyperchaotic map and the construction of optical fiber secure communication system - LI Chunbiao; LI Yongxin; ZHONG Qing; YANG Yong; AKGUL Akif (Tongxin xuebao)
A discrete hyperchaotic map was constructed by introducing nonlinear feedback of the square memristor function, which has the properties of total amplitude control, partial amplitude control, and direct offset boosting of hyperchaotic sequences. The controllability of chaotic map was achieved through the resistance function of a discrete memristor and the integral velocity of the internal variable. The simple constraint relationship from the memristor also gives the possibility of direct offset boosting. By introducing an additional constant parameter, direct offset boosting of a one-dimensional state variable can be obtained. Based on the RISC-V microcontroller of CH32V307, the proposed controllable hyperchaotic map was realized, and National Institute of Standards and Technology (NIST) testing proves the pseudo-random feature of hyperchaotic sequences. Based on the above hyperchaotic map, a physical layer scheme of orthogonal chirp division multiplexing-non-orthogonal multiple access (OCDM-NOMA) with encryption was constructed. The test of error rate in the process of 2 km communication with coupled seven core optical fiber was completed, further proving that the data transmission and decryption is reliable in the OCDM-NOMA system with hyperchaotic encryption, where data security is effectively protected.